Stochastic frontier models with dependent errors based on normal and exponential margins - Emilio Gómez-Déniz; Jorge V. Pérez-Rodríguez (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2017)
Following the recent work of Gómez-Déniz and Pérez-Rodríguez (2014), this paper extends the results obtained there to the normal-exponential distribution with dependence. Accordingly, the main aim of the present paper is to enhance stochastic production frontier and stochastic cost frontier modelling by proposing a bivariate distribution for dependent errors which allows us to nest the classical models. Closed-form expressions for the error term and technical efficiency are provided. An illustration using real data from the econometric literature is provided to show the applicability of the model proposed.
Keywords: C01; C13; C21; C51; 330; technical and cost efficiencies; stochastic frontier; marginal distribution; dependence; Sarmanov model